Biocontrol of Beauveria bassiana Against Leptocorisa acuta in Rice (Oryza sativa) - Gen Adi Wisanggeni; Febry Nurhidayati (Jurnal Biologi Tropis, 2026)
The rice bug (Leptocorisa acuta) is a major pest during the grain filling stage of rice (Oryza sativa L.), causing significant yield losses. The use of entomopathogenic fungi such as Beauveria bassiana offers an environmentally friendly alternative for pest control. This study aimed to evaluate the effectiveness of B. bassiana against rice bug under screen house conditions. The experiment was conducted by applying a suspension of B. bassiana (100 g formulation per liter of water) through direct spraying on rice plants infested with 11 adult rice bugs. Observations were conducted for seven days after application. Results showed that mortality began on the third day after treatment and reached 45.45% by the sixth day. Infected insects exhibited reduced movement, decreased feeding activity, body discoloration, and external white mycelial growth. Laboratory confirmation showed typical morphological characteristics of B. bassiana. These results indicate that B. bassiana has potential as a biological control agent against rice bug, although further studies with larger sample sizes and statistical analysis are required to optimize its field application.